Examining the consequences of leadership behaviour, self-efficacy and psychological climate with job satisfaction and work engagement on organizational values in hotel industry / Leila Radmand - Radmand, Leila (2017)
Organizational values develop organizational norms, guidelines, or expectations that prescribe appropriate kinds of behaviour by employees in particular situations, and dictate the behaviour of organizational members towards each other. The rapid development of hotels in Malaysia prompted the industry to be more aggressive towards maintaining customer loyalty while retaining a major part of the market share. Hotels need to allow the talents of their employees to flourish in order to realize peak performance. Operational employees play a pivotal role in delivering superior service quality to customers or converting aggrieved customers into satisfied and loyal ones. Employees are critical to service brand success, as their performance brings value promises to life. This study will provide helpful implications for both theoretical contribution and managers wishing to embed a set of values to help hotels recover from damaged customer relationships and rebuild consumer trust. Evaluating leadership, organization, and employee behaviour as a strategic tool plays a significant role for hotels to improve organizational values. The main objective of this study is to examine the predictors of hotel employee included; leadership behaviour (initiating leadership and consideration leadership), self-efficacy, and psychological climate (internal service and communication) on the adoption of organizational values, and the mediating role of job satisfaction and work engagement. Specifically, it aims to examine the relationship between the research variables; whether job satisfaction and work engagement mediate the effect of independent variables such as (leadership behaviour, self-efficacy, and psychological climate) on the dependent variable (organizational values). The sample size was 367 hotel employees in 4 and 5 star hotels in Kuala Lumpur, Malaysia. Data has been collected via the usage of questionnaires. There are seven parts in the findings detailing the relationship between the study variables and the role of the mediating variables. Initiating leadership, internal service, and communication was found to have significant relationship with organizational values. Initiating leadership and communication also were significantly related to job satisfaction. Initiating leadership, consideration leadership, self-efficacy, and communication were significantly related to work engagement. Job satisfaction and work engagement were found to have significant relationship with organizational values. Work engagement was found to have significant relationship with job satisfaction. Findings show that job satisfaction mediates the effect of initiating leadership and communication on organizational values. Findings also indicates work engagement mediates the effect of role initiating leadership, consideration leadership, self-efficacy, and communication on organizational values. In conclusion, this study has reinforced the constructs from leadership, employee, and adoption of values in the hotel industry. Thus, employers should investigate the values of the employees and synchronise them with the organization's values to affect the best possible match between employees and organizations.